APLIKASI SIMULASI MEMBUAT SIM C BERBASIS ANDROID - Achmad Syaiful Anam; Retno Wardhani; Masruroh Masruroh (Universitas Islam Lamongan, 2017)
Driving license is a registration proof and identification that is given by Indonesian Nation Police to someone who is fulfilled the administrative requirement, physically and mentally healthy, understand the traffic regulation, and skilled motorcycle driving. The survey result shows that not all people who have motorcycle have C driving license, eight of ten people say that they are afraid and have not understood the procedure of making C driving license yet. The motorcycle driver ha ve not passed the C driving license test frequently because they have not understood the theory of traffic sign and road marking, and driving the motorcycle yet. Based on that problem C Driving license Simulation Application Android Based is made as the research tittle. This application is developed based on Construct 2, the stages of developing Application is started from collecting the data (color-blind test, theory test, practice test’s information, and driving license information), then designing the pr ogram’s interface and program system’s groove, and the last one is black box testing and user testing. The implementation result of internal test (developing) Application test is based on Black Box method. Implementation result of user test based on the qu estionnaire from 50 respondents used likert scale was gotten 89%. So, it can be concluded that C Driving license Simulation Application is the good one